Digital development, environmental regulation, and electric power utilization efficiency - Zhang, Hui; Ou, Qinghai; Yuan, Xiaohui; Hu, Jian; Tang, Wenguang (Frontiers in Environmental Science, 2023)
To discuss whether digital development can effectively improve Chinese electric power utilization efficiency, this paper measures the electric power utilization efficiency of 30 Chinese provinces from 2011 to 2020, and constructs a regression model based on theoretical analysis. The moderating role of environmental regulation is also studied, and finally the robustness of the results is examined. The empirical evidence yields the following conclusions: (1) Digital development has a significant positive impact on the electric power utilization efficiency in China; (2)The moderating effect analysis and heterogeneity analysis show that stronger environmental regulation can promote the improvement of electric power utilization efficiency; the intensity of the impact of digital development on electric power utilization efficiency in eastern, central and western China is different, and the effect is especially obvious in the western region; (3)In addition, both the increase of electricity price related index and the increase of R&D expenditure have positive effects on the improvement of electric power utilization efficiency, but the increase of the share of secondary industry will have negative effects on electric power utilization efficiency.